2013 Asia-Pacific Microwave Conference Proceedings (APMC) 2013
DOI: 10.1109/apmc.2013.6694849
|View full text |Cite
|
Sign up to set email alerts
|

Graphene materials and devices for terahertz science and technology

Abstract: This article reviews recent advances in graphenebased materials and devices for terahertz science and technology. The fundamental basis of the optoelectronic properties of graphene is first introduced. Then the synthesis and crystallographic characterization of graphene materials, particularly focused on the authors' original heteroepitaxial graphene-on-silicon technology, are briefly described. Then nonequilibrium carrier relaxation and recombination dynamics in optically or electrically pumped graphene is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Due to a fast intraband relaxation (ps or less) and relatively slow interband recombination ()1 ps) of photoelectrons/holes, the population inversion is obtainable, as seen in Fig. 2 [39], [43]- [45].…”
Section: A Theorymentioning
confidence: 97%
See 2 more Smart Citations
“…Due to a fast intraband relaxation (ps or less) and relatively slow interband recombination ()1 ps) of photoelectrons/holes, the population inversion is obtainable, as seen in Fig. 2 [39], [43]- [45].…”
Section: A Theorymentioning
confidence: 97%
“…The authors have first analytically found the possibility of terahertz gain in such systems under cryogenic conditions [12] and have recently numerically verified the occurrence of the terahertz gain even at 300 K [39]- [41]. The authors recently succeeded in observation of amplified stimulated terahertz emission in exfoliated monolayer graphene and heteroepitaxial multilayer graphene pumped by an infrared femtosecond pulse laser at room temperature, testifying to the occurrence of the terahertz negative conductivity [42]- [45]. Such an active mechanism can be utilized for creating the graphene-based coherent laser sources of terahertz radiation [14], [24]- [26].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For wider strips one can disregard these edge effects and use the electron conductivity model developed for infinite graphene layer. In the THz range which is actively explored in today's electromagnetic-wave technology, various graphene based sources, circuits and systems are anticipated and developed [1].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the mediocre quality of initial GOS, recent improvements in GOS technology now provide a material that clearly demonstrates the linear dispersion of the π band near the Dirac point by angle-resolved PES21. The potential of GOS for electronic and photonic device applications has been demonstrated by fabricating transistors2223, terahertz photonic devices24 and even logic inverters25, a fundamental component for integrated circuits. GOS is thus becoming a promising graphene production method, based on its advantages, such as the cost of the wafer and compatibility with existing Si-based device technologies.…”
mentioning
confidence: 99%